Root fracture in the permanent maxillary central incisors: a case report of 10 years follow-up - Thais Cougo Gomes; Mariela Padovese; Juliano Pelim Pessan; Robson Frederico Cunha (Asociación Latinoamericana de Odontopediatría, 2022)
The objective of this case report is to present a 9-year-old female patient who suffered horizontal root fracture in the middle third of the two upper central permanent incisors. The teeth were splinted with composite resin in the proximal teeth involved in the trauma. After, the patient was referred to the pediatric dentistry clinic, where she received clinical and radiographic care for a period of ten years. Endodontic intervention was not necessary on both central incisors teeth. Tooth 11 healing by interposition of bone and connective tissue, and teeth 21 healing by interposition of connective tissue. After ten years, the teeth presented without any significant signs or symptoms requiring an invasive intervention. It is concluded that the patient's cooperation regarding care, oral hygiene and attendance at the return appointments, can be decisive for the success of the treatment.